2002
DOI: 10.1046/j.1359-4117.2002.01038.x
|View full text |Cite
|
Sign up to set email alerts
|

Discovery and development of anticancer agents from plants

Abstract: A novel in vitro assay for the discovery of anticancer agents was used to examine aqueous and organic extracts from 1847 plants collected mainly in the U.S. Southwest and West. The assay results were separated into 5 categories: inactive (62%), equally active (36%), equally active and potent (0.5%), solid tumor selective (1.4%), and human selective (0.8%). Extracts from the latter three categories were fractionated using the in vitro assay to biodirect each step. Psorothamnus emoryi extracts were solid tumor s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
93
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(93 citation statements)
references
References 12 publications
0
93
0
Order By: Relevance
“…02172; collection locale: Milne Bay, Papua New Guinea) displayed potent cytotoxicity in a primary screen using leukemia and solid tumor murine and human cancer cell lines (Table 1). 18 This prompted the growth of a larger-scale culture (20 L) to facilitate the purification of metabolites from dichloromethane-soluble broth (EFD) and mycelial extracts (TFD) (Table 1, Figure S1). Bioassay against a murine lymphocytic cell line (L1210) and Staphylococcus epidermidis and NMR data were used to guide the fractionation, resulting in two new related linear octapeptides, RHM1 (1) and RHM2 (2), and the known peptaibiotic efrapeptin G (3).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…02172; collection locale: Milne Bay, Papua New Guinea) displayed potent cytotoxicity in a primary screen using leukemia and solid tumor murine and human cancer cell lines (Table 1). 18 This prompted the growth of a larger-scale culture (20 L) to facilitate the purification of metabolites from dichloromethane-soluble broth (EFD) and mycelial extracts (TFD) (Table 1, Figure S1). Bioassay against a murine lymphocytic cell line (L1210) and Staphylococcus epidermidis and NMR data were used to guide the fractionation, resulting in two new related linear octapeptides, RHM1 (1) and RHM2 (2), and the known peptaibiotic efrapeptin G (3).…”
Section: Resultsmentioning
confidence: 99%
“…Efrapeptin G (3) was slightly less active against S. epidermidis (MIC 80 μg/mL, Table 1), while RHM2 (2) did not exhibit antimicrobial activity (MIC > 400 μg/mL, Table 1). Both 1 and 2 exhibited mild cytotoxicity against murine L1210 cells in a disk diffusion soft agar colony-forming assay 18 (Table 1). Alternatively, 3 exhibited potent cytotoxicity against murine L1210 cells and against HCT-116 with an IC 50 of 3.5 × 10 -3 μg/ mL.…”
Section: Resultsmentioning
confidence: 99%
“…The methanol-soluble fraction, coded XFM, had selective bioactivity (for murine adenocarcinoma C-38 cell line) in the disk diffusion solid tumor whole cell assay with an inhibitory zone differential of 9 mm between murine C-38 and CFU-GM cells at 180 µg per disk. 14 Because of this selective bioactivity, the MeOH fraction was subjected to HPLC purification to afford five fractions ( Figure S2). Fraction 3 was pure leucosolenamine A (5) (5.6 mg) with an m/z of 384.2 [M + H] + (ESI-TOF) and exhibited inhibition zones of 10.5 mm (at 180 µg per disk) against murine colon 38 (vs 0 mm against CFU-GM).…”
Section: Resultsmentioning
confidence: 99%
“…These were confirmed by gHMBC correlations as illustrated in Figure 1, substructure B, and in Figure 5 Our investigation of the biological properties was restricted to an evaluation of 5 due to sample limitation and stability. The data set summarized in Table 3 employed our standard disk diffusion assay 14 and revealed that 5, at 180 μg/disk, inhibited murine C-38 cells with a 10.5 mm zone as compared to 0 mm against CFU-GM cells. This is the profile for a mildly potent selective cytotoxin when compared to the in vivo active agent bengamide E, 20 displaying at 7.8 μg/disk inhibition zones of 21 mm against C-38 and 16.5 mm against CFU-GM cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation